Leptin Deficiency: Addressing the Detrimental Effects of Stringent Calorie Restriction on Reproductive-Age Women through Patient Education and Counselling - Sarvesh Sabarathinam,; Prabhakaran A K,; Vinitha Packirisamy,; Lakshmi Thangavelu, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Stringent calorie restriction, often pursued for weight loss, has significant repercussions for metabolic and reproductive health, primarily due to leptin deficiency (LD). Leptin is essential for regulating appetite, metabolism, and reproductive functions. This review explores the effects of LD from aggressive dieting on women's reproductive health and highlights the role of clinical pharmacists in managing these issues through patient education and counseling. This narrative review examines existing literature on leptin’s role in female reproduction, its influence on puberty, menstruation, and energy balance, and assesses various dietary approaches affecting leptin levels. Caloric restriction significantly lowers leptin levels, disrupting the hypothalamic-pituitary-ovarian (HPO) axis, which impacts reproductive functions, delays puberty, and causes menstrual irregularities. LD also disrupts energy balance and can lead to broader metabolic disturbances. The review delves into the physiological impact of LD on reproductive health, including its effects on follicular development, endometrial function, and overall metabolism. It underscores the crucial role of healthcare professionals, especially clinical pharmacists, in managing these challenges through comprehensive patient care. Managing LD in women undergoing severe calorie restriction requires a multidisciplinary approach, including personalized nutrition plans, digital monitoring tools, and behavioral support. Clinical pharmacists are vital in patient education and collaborative care to mitigate the adverse effects of restrictive dieting.